Socio-Legal Review of The Implementation of Identification and Inventory of Communal Intellectual Property for Tourism Development - Atsar, Abdul; Surya, Ida; Nugraha, Lalu Guna; Jha, Saroj (SASI, 2025)
Introduction: Communal Intellectual Property can be used to support the development of Intellectual Property-based Tourism.Purposes of the Research: The purpose of this study is to examine the effectiveness of the law in implementing the Identification and Inventory of Communal Intellectual Property as a form of preventive legal protection for Communal Intellectual Property (IPR) and government efforts in implementing the Identification and Inventory of Communal Intellectual Property to support Intellectual Property-based Tourism Development.Methods of the Research: The research method used in this study is a socio-legal approach. The data analysis technique used is a qualitative descriptive analysis technique.Results of the Research: The implementation of the Identification and Inventory of Communal Intellectual Property in Central Lombok Regency has not been effective. This is because the identification and inventory of Communal Intellectual Property (CIP) has not been implemented in an orderly manner by the local government/community so that legal certainty and justice are achieved for CIP owners/Communal communities. The Government Regulation has not been complied with and enforced. There is a discrepancy between the rules and their implementation. In addition, the level of community compliance, Law enforcement by law enforcement officers also has a major influence on the effectiveness of the law. Government efforts to overcome the ineffective implementation of Identification and Inventory, include making Regional Regulations that require each Village to identify and inventory Communal Intellectual Property, establishing Partnerships and Cooperation with third parties or managers in utilizing Communal Intellectual Property for the development of Intellectual Property-based tourism, Regional Governments must encourage investors to invest their capital in building Infrastructure and Facilities for Tourism Destinations based on Intellectual Property, Utilizing Technology and Digital Marketing for the development of Intellectual Property-based Tourism, and Regional Governments must focus and pay special attention to the Intellectual Property-based tourism industry.